Solve the system of linear equations using elimination.


−7x + 3y = −6

−3x + 3y = 6


A) (3, 5)

B) (3, −5)

C) (−3, 5)

D) (−3, −5)

Respuesta :

Answer:

Option A) x = 3 and y = 5

Step-by-step explanation:

−7x + 3y = −6_____ first equation

−3x + 3y = 6_____ second equation

Since both equations have "y" that share the same coefficients (that is 3),we can solve this equation.

---First step is to subtract the equation 2 from 1

−7x + 3y = −6

−3x + 3y = 6

From the above equation, we have

-4x = -12

Divide both sides by -4

X = 3

--- Substitute x = 3 in equation 1

−7x + 3y = −6

-7(3) + 3y = -6

-21 + 3y = -6

3y = 21 - 6

3y = 15

Y = 5

X = 3 and y = 5( option a)